Uma análise sobre aquisição e criação de conhecimento na produção de fármacos similares - Menezes, Nayra Karinne Bernardes de (Universidade do Vale do Rio dos Sinos, 2010)
This study intends to analyse how to acquire and create knowledge to improve the production process of medicines which are out of patent protection rules. It intends to contribute to the discussion about relations between imitation and innovation in industrial production. Medicines which are out of patent rules have been competing on a basis of price rather than on innovation. However, considering that even if competition is not based on innovation, knowledge resources are needed to improve the production processes of these medicines as a way to achieve an optimal balance between price and quality. This study investigates the specific strategic skills and kinds of knowledge that have been used in this particular case. Empirical data was obtained from labs situated at Anapolis District (DAIA, Brasil), which is the main cluster of industries dedicated to the production of medicines that are out of patent rules in Latin America. Data was collected through interviews, documents analysis and direct observation. The evidences show that scientific and technological knowledge have been improved on the production of these medicines. This improvement depends on internal resources of the lab as well on the interaction with external sources as research institutes and Universities. Finally, the study suggests that all the processes required to imitate dominated formulas of medicines which are out of patent rules contribute to build capabilities related to innovation.
Keywords: Conhecimento; Imitação; Produção de farmacos; Knowledge creation; Imitation; Medicines production; ACCNPQ::Ciências Sociais Aplicadas::Administração